2016
DOI: 10.1177/0954405415599927
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and optimization of cutter geometric parameters for surface integrity in milling titanium alloy using a modified grey–Taguchi method

Abstract: Surface integrity determines the performance and quality of the end product. It often needs to change the input parameters, such as cutting parameter, cutting tool geometry and material, and tool coating, to obtain the best machining surface integrity. This article presents and demonstrates the effectiveness for the multi-objective optimization of cutter geometric parameters for surface integrity of milling Ti-5Al-5Mo-5V-1Cr-1Fe titanium alloy via grey relational analysis coupled with the Taguchi method, entro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 34 publications
(36 reference statements)
0
13
0
Order By: Relevance
“…The rake angle of cutting tools has a critical influence on residual stress. 25 The cutter with a more effective negative rake angle and higher thermal conductivity generate more compressive residual stress. 26…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rake angle of cutting tools has a critical influence on residual stress. 25 The cutter with a more effective negative rake angle and higher thermal conductivity generate more compressive residual stress. 26…”
Section: Resultsmentioning
confidence: 99%
“…The rake angle of cutting tools has a critical influence on residual stress. 25 The cutter with a more effective negative rake angle and higher thermal conductivity generate more compressive residual stress. 26 For the M/MP/MH group, as shown in Figure 9(a), polishing completely removes the tensile stress of the sample M. The residual stress of sample MP is -834 MPa at the surface and monotonically decreases to 0 MPa at a depth of 80 mm.…”
Section: Surface and Subsurface Residual Stressmentioning
confidence: 99%
“…Abbasi et al investigated the influence of changing the rake angle of the PCD insert on cutting forces, tool-chip interface temperature, and tool stresses and compared the results with a TiAIN coated carbide inserted end mill utilizing FEM. The result showed that the tool rake angle has significant influence and reveals a difference in the performance for the two kind of inserts [5]. Other researchers have analyzed tool wear mechanisms of machining titanium alloys.…”
Section: Introductionmentioning
confidence: 98%
“…Ratnam et al (2016) studied the turn-milling process in tangential and orthogonal directions to minimize the surface roughness of extruded brass material. Several recent works focussed on the optimal machining parameters for multi-pass milling operations by considering the statistical and artificial intelligent techniques (Wang et al 2005;Sukumar et al 2014;Venkata Rao and Pawar 2010;Das et al 2016;Ren et al 2016). The efficiency of a neural network model was estimated by conducting the numerical simulations and experiments.…”
Section: Introductionmentioning
confidence: 99%